Proyecto de factibilidad para la producción y comercialización de gel hidratante a base de aloe vera para damas en la ciudad de Loja. - Orellana Piedra, Luis Daniel (2024)
The research project focuses on evaluating the feasibility of producing and marketing a moisturizing gel for women in the city of Loja. Four objectives have been defined for its development: the market study, in which the analysis of supply and demand will be carried out; the technical study, which is essential to know the size, location, project engineering and organizational design; the financial study, in which the necessary investment, available financing, costs involved, projected income and break-even point of production will be identified; and finally, through the financial evaluation and its indicators, the viability of the investment proposal will be evaluated. The research methodology used was mainly deductive, non-experimental and descriptive. A quantitative approach was used together with data collection techniques such as surveys and literature reviews. The results used to determine the feasibility of the project are based on: the Net Present Value (NPV) of $39,847.28, which is a positive NPV; the Internal Rate of Return (TIR) of 47,35%, which is higher than the opportunity cost rate; the Capital Recovery Period (CRP), which is 2 years, 11 months and 4 days; the Benefit/Cost Ratio (BCR), which indicates that the company will achieve a profitability of 0.30 cents for every dollar invested; and the Sensitivity Analysis (SA), which indicates that the project supports a cost increase of 12,96% and a revenue decrease of 10,27%. Therefore, based on the respective financial analysis, it is determined that the project is feasible for its respective implementation.